Self-Control and Skincare Consumptive Behavior in E-Commerce: A Study on Male College Students in Islamic Perspective - Rismawati, Graphy; Warastri, Annisa (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
Examining the connection between self-control and skincare use among male students who shop online was the primary goal of this research. In order to find out if there is a connection between variables or not, or to make predictions based on the correlation between variables, this study uses a quantitative approach with a correlational approach. Accidental sampling, a convenience-based sampling approach, was used as the sample methodology. In all, 160 men participated in the survey. The hypothesis testing results show that rxy has a value of -0.0881 and a p-value of 0.000, which is less than 0.001. As a result of this condition, it is clear that there is a strong inverse link between self-control and consumptive behavior. In other words, a lack of self-control may cause one to be very consumptive, and vice versa. Among male students who shop for skincare online, the findings reveal a strong inverse correlation between self-control and consumptive behavior. The significant negative association between the two variables is shown by the correlation coefficient value of -0.881. Lower levels of self-control are associated with greater levels of consumptive behavior, while higher levels of self-control are associated with lower levels of consumptive behavior.